CHANGING PARADIGMS IN PREOPERATIVE FASTING: RESULTS OF A JOINT EFFORT IN PEDIATRIC SURGERY - CARVALHO,Carlos Augusto Leite de Barros (2017)
ABSTRACT Background: Current researches associate long fasting periods to several adverse consequences. The fasting abbreviation to 2 h to clear liquids associated with the use of drinks containing carbohydrates attenuates endocrinometabolic response to surgical trauma, but often is observed children advised to not intake food from 00:00 h till the scheduled surgical time, regardless of what it is. Aim: To evaluate the safety of a protocol of preoperative fasting abbreviation with a beverage containing carbohydrates, and early postoperative feeding in children underwent elective small/mid-size surgical procedures during a national task-force on pediatric surgery. Methods: Thirty-six patients were prospectively included, and for several reasons five were excluded. All 31 who remained in the study received a nutritional supplement containing 150 ml of water plus 12.5% maltodextrin 2 h before the procedure. Data of the pre-operative fasting time, anesthetic complications and time of postoperative refeeding, were collected. Results: Twenty-three (74.2%) were males, the median age was 5 y, and the median weight was 20 kg. The median time of pre-operative fasting was 145 min and the time of post-operative refeeding was 135 min. There were no adverse effects on the anesthetic procedures or during surgery. Post-operatively, two children (6.5%) vomited. Conclusion: The abbreviation of pre-operative fasting to 2 h with beverage containing carbohydrate in pediatric surgery is safe. Early refeeding in elective small/mid-size procedures can be prescribed.